Classification of aorta doppler signals using variable coded-hierarchical genetic fuzzy system - Güler, I; Hardalaç, F; Ergün, E; Barisçi, N (Pergamon-Elsevier Science Ltd, 2004)
In this study, Doppler signals, recorded from the output of aorta valve of 80 patients, were transferred to personal computer via 16 bit sound card. The fast Fourier transform (FFT) method was applied to the recorded signal from each patient. Since FFT method inherently cannot offer a good spectral resolution at highly turbulent blood flows, it sometimes causes wrong interpretation of cardiac Doppler signals. In order to avoid this problem, two known diseased heart signals such as aorta stenosis and aorta insufficiency were introduced to two different genetic fuzzy systems. The disadvantages arise from these two different genetic fuzzy systems were eliminated by using the new genetic fuzzy system which is proposed in this study. The proposed genetic fuzzy system is called as variable coded-hierarchical genetic fuzzy system. As a result, it is shown that the proposed system decreases the computational time since it uses less genes. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: fast Fourier transform method; cardiac doppler; aorta stenosis; aorta insufficiency; genetic fuzzy system; hierarchical genetic fuzzy system; variable coded-hierarchical genetic fuzzy system